2019
DOI: 10.1101/590497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain connectivity measures improve modeling of functional outcome after acute ischemic stroke

Abstract: Background : The ability to model long-term functional outcomes after acute ischemic stroke (AIS) represents a major clinical challenge. One approach to potentially improve prediction modeling involves the analysis of connectomics. The field of connectomics represents the brain's connectivity as a graph, whose topological properties have helped uncover underlying mechanisms of brain function in health and disease. Specifically, we assessed the impact of stroke lesions on rich club (RC) organization, a high cap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…Our finding that this cortical association network has decreased connectivity in children with SCD compared with controls suggests a plausible mechanism for the cognitive impairments prevalent in SCD. Functional connectivity has been shown to predict clinical outcomes in patients with neurological disease, including stroke 48 and Alzheimer's disease 49 . A sensitive preclinical biomarker for the cognitive complications of SCD could improve risk stratification of patients with SCD for curative interventions, such as stem cell transplant or gene therapy trials.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that this cortical association network has decreased connectivity in children with SCD compared with controls suggests a plausible mechanism for the cognitive impairments prevalent in SCD. Functional connectivity has been shown to predict clinical outcomes in patients with neurological disease, including stroke 48 and Alzheimer's disease 49 . A sensitive preclinical biomarker for the cognitive complications of SCD could improve risk stratification of patients with SCD for curative interventions, such as stem cell transplant or gene therapy trials.…”
Section: Discussionmentioning
confidence: 99%
“…ref. 36 for a comparable approach) or dynamic estimates (dwell times for State 1–3, the acute dynamic model). We did not integrate fraction times in addition to dwell times to reduce probable collinearity of input variables.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…With regard to the cognitive control and default mode networks: These domains are well known to encompass cortical hubs that are globally well-connected and essential to orchestrate various brain functions 50,51,52 . Recent stroke studies relying on structural MRI data already indicated worse stroke outcomes the more of such well-connected areas were affected by stroke lesions 36,53 . Previous functional MRI studies have also reported disturbed functional connectivity within the default mode network when comparing subacute ischemic stroke patients and healthy controls, independent of any specific deficits or stroke severity ( 54 : decreased left medial temporal lobe, posterior cingulate and medial prefrontal cortical areas, 10 : decreased posterior cingulate cortex/precuneus, increased medial prefrontal cortex, left hippocampus).…”
Section: Alterations In Dynamic Connectivity: Recovery Of Stroke Sevementioning
confidence: 99%
See 2 more Smart Citations